Pengaruh Beban Kerja Terhadap Stres Kerja pada Pekerja Karyawan Gen Z - Ega Nopiyanti Andriyansyah; Arif Rahman Hakim; M. Choirul Ibad (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In the era of globalization and the industrial revolution 4.0, companies are required to increase efficiency and productivity through innovative and creative human resources. However, high work demands often add to the burden on employees, where approximately 8% of global workers experience work stress. This study aims to determine the effect of workload on work stress in Generation Z employees in Indonesia. The method used is a quantitative approach with a cross-sectional design, involving 388 respondents selected by purposive sampling. Workload adapted the Cognitive and Emotional Demands Questionnaire (CarMen-Q) measuring tool, while work stress adopted the Perceived Stress Scale (PSS-10) measuring tool. The results of a simple linear regression analysis processed using SPSS version 27 showed a significant effect of workload on work stress with a positive direction of 0.458, which means that the higher the workload experienced, the higher the level of work stress felt by Generation Z employees. then workload has a contribution of 77.8%.